A study on the pharmacokinetic bioequivalence of oral tablet formulations of riluzole among healthy volunteers utilizing HPLC-MS/MS - Fei Yu; Rui Wang; Keli Wang; BoYang Lin; Xuan Zhou; Linghong Chen; Li Ma; Zheng Liao; Wanggang Zhang (BMC Pharmacology and Toxicology)
Abstract Introduction This randomized, open-label, two period, two treatment, fasting bioequivalence trial was conducted to demonstrate the bioequivalence between riluzole tablets manufactured by Jiangsu Enhua Pharmaceutical Co., Ltd. and the reference preparations from Sanofi Winthrop Industry (certified by Sanofi Mature IP) in healthy individuals. Objective The study aimed to compare the pharmacokinetic parameters and evaluate the bioequivalence of both preparations when taken on an empty stomach. Additionally, the safety profile of both preparations was assessed in the study population. Methods Seventy-two subjects participated in the trial and received riluzole tablets once per dosing cycle while fasting. They were randomLy assigned to either a 50-mg test or reference formulation, with a 7-day washout period between cycles. Venous blood samples (4 mL) were collected 22 times from each subject, starting before dosing (0 h) and ending 48 h after. Plasma riluzole concentrations were measured using liquid chromatography tandem mass spectrometry. This clinical trial has been officially registered in the Chinese Clinical Trial Register (accessible at http://www.chinadrugtrials.org.cn/index.htmL ) with the registration number CTR20230637 on March 02, 2023. Results The results showed that the geometric mean ratios of key pharmacokinetic parameters—including the area under the plasma concentration-time curve from time zero to the last nonzero concentration (AUC0 − t) (102.21%; confidence interval [CI], 96.85-107.86%), AUC from time zero to infinity (AUC0−∞) (102.03%; CI, 96.86-107.47%), and the peak plasma concentration (Cmax) (107.47%; CI, 95.03-121.54%)—all fell within the bioequivalence acceptance range of 80-125%. Importantly, no serious adverse events were reported, and no subjects withdrew due to adverse events, indicating good tolerability of both formulations among the healthy Chinese volunteers. Conclusion These findings establish the bioequivalence of the 50-mg test preparation of oral riluzole tablets with the reference listed drug.